Gender Equality and Economic Growth: An Econometric Analysis using World Development Indicators - Sehar, Najmus; Bhatia, Shivangi; Sharma, Mona (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study investigates the impact of gender equality on economic growth using panel data from the World Development Indicators (2000–2023). It employs econometric techniques to analyze the influence of key gender-related variables female labor force participation, secondary school enrollment, and women’s representation in national parliaments on GDP per capita, alongside gross capital formation as a control. Findings reveal that female secondary education is the most significant contributor to economic growth, with a 1% increase resulting in a 269 rise in GDP per capita. Although female labor force participation and political representation showed positive correlations, their effects were statistically insignificant, indicating deeper structural barriers. Gross capital formation positively influenced GDP growth, confirming its foundational economic role. The results underscore the necessity for inclusive education policies, while also highlighting the need for broader systemic reforms in labor and governance to harness the full economic potential of gender equality.